A new class of ultrafine anaphase bridges generated by homologous recombination. Issue 17 (2nd September 2018) - Chan, Ying Wai; West, Stephen C.
ABSTRACT: Ultrafine anaphase bridges (UFBs) are a potential source of genome instability that is a hallmark of cancer. UFBs can arise from DNA catenanes at centromeres/rDNA loci, late replication intermediates induced by replication stress, and DNA linkages at telomeres. Recently, it was reported that DNA intertwinements generated by homologous recombination give rise to a new class of UFBs, which have been termed homologous recombination ultrafine bridges (HR-UFBs). HR-UFBs are decorated with PICH and BLM in anaphase, and are subsequently converted to RPA-coated, single-stranded DNA bridges. Breakage of these sister chromatid entanglements leads to DNA damage that can be repaired by non-homologous end joining in the next cell cycle, but the potential consequences include DNA rearrangements, chromosome translocations and fusions. Visualisation of these HR-UFBs, and knowledge of how they arise, provides a molecular basis to explain how upregulation of homologous recombination or failure to resolve recombination intermediates leads to the development of chromosomal instability observed in certain cancers.